Ultrasonographic Findings of Periarthritis of Shoulder Joint in the Out Patients Department (KYAMC Journal, 2022)
Background: To detect periarticular lesions around the shoulder, musculoskeletal ultrasonography is very much useful. Recent improvements in Ultrasonographic technology have led to a higher sensitivity and accuracy of musculoskeletal sonography.Objective: To present the distribution and representation of shoulder ultrasonographic (US) examination findings in patients with clinical diagnosis of shoulder periarthritis.Materials and Methods: A cross sectional descriptive type of study at Single center setting conducted in OPD of department of Physical Medicine& Rehabilitation, BSMMU, Dhaka on thirty-five patients with the clinical diagnosis of periarthritis of shoulder. Data was collected using an interview- administered questionnaire. All baseline investigations were done. Ultrasonogram was done by experienced Sonologists who were unaware about clinical data.Results: The primary end point was reached in 85 percent of patient presented sonographic alteration suffering from periathritis of shoulder. The structure most frequently involved was bicipital tendinitis (32%) and Supraspinatus tendinitis (28%). Sub acromial Bursitis (14%) and Acromioclavicular Osteoathritis (11%) were also involved. About 15% individual presents no abnormalities. Different varieties of changes in the various structures had been detected.Conclusion: Proper identification and assessment of the alteration of periarticular structure helps to approach for management and rehabilitation of Periarthritis of shoulder thus disability can be reduced.KYAMC Journal Vol. 13, No. 03, October 2022: 134-138